1992
DOI: 10.1152/ajpcell.1992.262.1.c128
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between cAMP and ATP in signal transduction in cardiac myocytes

Abstract: ATP transiently increases the intracellular Ca2+ concentration in cardiac myocyte suspensions. Pretreatment with norepinephrine (NE) greatly potentiates the ATP response. We performed experiments on adult rat myocyte suspensions loaded with fura-2 to investigate the mechanism of NE potentiation. We found that forskolin (an activator of adenylate cyclase), 3-isobutyl-1-methylxanthine (an inhibitor of phosphodiesterase), and permeative adenosine 3',5'-cyclic monophosphate (cAMP) analogues potentiate the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The isoproterenol-mediated increase in [Ca 2ϩ ] i , unlike that due to ATP, was markedly inhibited by propranolol, indicating the involvement of ␤-ARs in the isoproterenol-mediated increase in [Ca 2ϩ ] i . Similarly, Zheng et al (36) have shown that the isoproterenol-induced increase in the ratio of changes in fluorescence level (⌬F ATP /⌬F KCl ) was significantly attenuated by propranolol after the addition of ATP and KCl. The effect of ␤-AR blockade on isoproterenol-induced Ca 2ϩ -mobilization may be of some specific nature because basal [Ca 2ϩ ] i remained unaltered in the presence of propranolol.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The isoproterenol-mediated increase in [Ca 2ϩ ] i , unlike that due to ATP, was markedly inhibited by propranolol, indicating the involvement of ␤-ARs in the isoproterenol-mediated increase in [Ca 2ϩ ] i . Similarly, Zheng et al (36) have shown that the isoproterenol-induced increase in the ratio of changes in fluorescence level (⌬F ATP /⌬F KCl ) was significantly attenuated by propranolol after the addition of ATP and KCl. The effect of ␤-AR blockade on isoproterenol-induced Ca 2ϩ -mobilization may be of some specific nature because basal [Ca 2ϩ ] i remained unaltered in the presence of propranolol.…”
Section: Discussionmentioning
confidence: 71%
“…The ATP-induced increase in [Ca 2ϩ ] i was also attenuated by treatment with these antagonists. Thus an increase in the amplitude of inward Ca 2ϩ current through the SL L-type Ca 2ϩ channels (36) and ␤-AR-cAMP-PKA pathway-mediated phosphorylation of L-type Ca 2ϩ channels (20) may be the mechanism of isoproterenol-and ATPmediated increase in Ca 2ϩ -influx. Although ␤-AR stimulationmediated Ca 2ϩ entry by L-type Ca 2ϩ channels has been linked with Ca 2ϩ release from the SR Ca 2ϩ stores (30), the isoproterenol-mediated potentiation of the ATP-induced increase in [Ca 2ϩ ] i seems to be independent of Ca 2ϩ release from the intracellular stores because ryanodine, an inhibitor of the SR Ca 2ϩ release channel (4,25), did not affect the isoproterenolmediated increase in [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that ATPo and catecholamines share common postreceptor transduction pathways. Given the fact that in many cell types ATPo and catecholamines can potentiate their individual effects (De Young & Scarpa, 1987;Zheng, Christie, De Young, Levy & Scarpa, 1992), and given that they are coreleased from noradrenergic terminals in the heart (Burnstock, 1981;Burnstock & Kennedy, 1986;see also Von Kiigelgen & Starke, 1991), the possibility must remain that much lower doses of both agents than hitherto tested, when combined, may influence acid extrusion from the cardiac cell. This raises the strong possibility that catecholamines may be important modulators of pHi regulation in the cardiac cell, not only under pathological conditions such as myocardial ischaemia and hypoxia (when local concentrations of catecholamines and ATPo may be extremely high; see Gordon, 1986 for review) but also under more normal physiological conditions.…”
Section: Ac-and F-modulation Of Cardiac Ph5mentioning
confidence: 99%